Effect of Additional Training and Activities on Science Teacher Modification Skills - Widia; Ari Widodo; Ida Kaniawati (Postgraduate, University of Mataram, 2025)
This study aims to answer research questions about: (a) Does the number of training sessions attended affect the modification skills of science teachers? and (b) Do additional activities affect the modification skills of science teachers? The study uses a qualitative method with a sequential explanatory approach using questionnaires and interviews as instruments. The subjects of this research are 12 elementary and junior high school science teachers who are members of subject teachers' deliberation groups. The results show that the teachers' ability to modify learning designs involving students is influenced by the number of training sessions and additional activities. The data indicates that the more teachers attend training sessions, the better they are at modifying learning materials involving students, meaning that training has a positive effect on improving the modification skills of science teachers. Conversely, the more additional activities teachers engage in, the lower their ability to modify learning materials involving students, indicating that excessive additional activities have a negative impact on the modification skills of science teachers.